Comparison of chemical characteristics in chips and porang flour typical East Kalimantan with commercial porang flour as a functional food - Anggela, Anggela; Nabila, Yamaysyah Salma; Ananda, Rahmatia; Nainggolan, Eris Pransiscah (Jurnal Agrotek Ummat, 2023)
Porang is a tuber which is abundantly in Indonesia, especially in the East Kalimantan region. However, the potential of porang tubers is still not widely known and optimally developed, particularly in product diversification. The stages in this research consist of making porang’s chips, making porang’s flour, physicochemical analysis of porang’s flour. Based on the research results, the yield of porang chips was 19.12% and porang flour was 23.5%. The color of the flour produced is bright yellow, due to the carotenoid content in porang tubers. The proximate content of flour is dominated by the highest nutritional content in protein content (12.34%), while other proximate contents are as follows water content (12.29%), ash content (7.85%), fat content (1.54%), and carbohydrate content (65.98%) . The high protein and low fat content produced in the research shows the potential for East Kalimantan porang flour to be developed into a functional ingredient which is beneficial for health.